Identifying structural defects in end-chain functionalised polyolefins and copolymers from chain walking polymerisation - Ndlovu, Petronella Zabesuthu (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.